Pregnancy-Associated Plasma Protein A Induces Inflammatory Cytokine Expression by Activating IGF-I/PI3K/Akt Pathways - Weiping Li; Hongwei Li; Li Zhou; Zijian Wang; Bing Hua (Mediators of Inflammation)
Pregnancy-associated plasma protein A (PAPP-A) was previously reported to be an inflammatory biomarker and a prognostic marker of acute coronary syndrome (ACS) and involved in the process of atherosclerosis and plaque rupture. However, the role of PAPP-A in inflammation is poorly understood. In this study, we aimed to investigate the role of PAPP-A in macrophage activation and inflammatory cytokine production. RAW264.7 macrophages were treated with or without PAPP-A. Reverse-transcriptase quantitative real-time PCR (RT-qPCR) and Western blot were performed to detect gene and protein expressions. The concentration of monocyte chemoattractant protein-1 (MCP-1), tumor necrosis factor-α (TNF-α), and interleukin-6 (IL-6) in culture supernatants was determined by ELISA. Results showed that PAPP-A significantly stimulated the expression of MCP-1, TNF-α, and IL-6 at both transcriptional and translational levels in a dose-dependent and time-dependent manner. The secretion of these inflammatory cytokines by macrophages was also increased after PAPP-A treatment. Moreover, PAPP-A activated the IGF-I/PI3K/Akt signaling pathway in macrophages. The PAPP-A-mediated upregulation of MCP-1, TNF-α, and IL-6 mRNA and protein levels were strongly inhibited by PI3K inhibitors or IGF-IR siRNA, indicating that the upregulation of MCP-1, TNF-α, and IL-6 could involve the IGF-I/PI3K/Akt pathway. Together, this study demonstrates that PAPP-A activates the macrophage signaling pathway (IGF-I/PI3K/Akt), which drives the expression and production of inflammatory cytokines known to contribute to the initiation and progression of ACS. These findings indicate that PAPP-A may play a proinflammatory role in the pathophysiology of ACS and serve as a potential therapeutic target.